2014
DOI: 10.3109/21678421.2014.886700
|View full text |Cite
|
Sign up to set email alerts
|

Psychological as well as illness factors influence acceptance of non-invasive ventilation (NIV) and gastrostomy in amyotrophic lateral sclerosis (ALS): A prospective population study

Abstract: Our objective was to identify factors associated with acceptance of non-invasive ventilation (NIV) and gastrostomy in an exploratory population-based study. Seventy-eight people with ALS at least six months post-diagnosis, and 50 caregivers, were recruited from the South-East ALS Register. Baseline physical, cognitive and psychological measures were obtained. Three-monthly follow-ups monitored whether patients had accepted or refused NIV or gastrostomy. Following an intervention decision, post-decision intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…PwALS were recruited from the South-East ALS register [41] as part of a larger, prospective study of decision-making about gastrostomy and NIV in ALS [17]. Inclusion criteria for this qualitative study were: confirmed diagnosis of ALS; duration of disease at entry into the larger study [17] between 6 and 60 months; and referral for NIV and/or gastrostomy, with a decision to either accept or decline the intervention.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…PwALS were recruited from the South-East ALS register [41] as part of a larger, prospective study of decision-making about gastrostomy and NIV in ALS [17]. Inclusion criteria for this qualitative study were: confirmed diagnosis of ALS; duration of disease at entry into the larger study [17] between 6 and 60 months; and referral for NIV and/or gastrostomy, with a decision to either accept or decline the intervention.…”
Section: Participantsmentioning
confidence: 99%
“…Inclusion criteria for this qualitative study were: confirmed diagnosis of ALS; duration of disease at entry into the larger study [17] between 6 and 60 months; and referral for NIV and/or gastrostomy, with a decision to either accept or decline the intervention. PwALS were not excluded on the basis of clinically-apparent cognitive impairment provided they could give valid informed consent.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations